Exploring the effect of auditory stimuli as environmental enrichment in a Holstein herd using glucocorticoids as biomarker - Van Marle-Koster, Este (University of Pretoria, 2022)
Thesis (MSc Agric (Animal Science: Animal Breeding and Genetics))--University of Pretoria, 2021.